Verzet tegen de politieautoriteit in Brussel (1945‑1975): gerechtelijke aanpak van het geweld van de lagere volksklasse - Melpomeni Skordou (Brussels Studies, 2012)
The study of the repression of resistance to the police in Brussels during the period between 1945 and 1975 invalidates the hypothesis of a phenomenon of rebellion among young people. The analysis of legal cases suggests that this resistance is the result of police interference in private conflicts. Men in their thirties who are most often from a disadvantaged background, frequent the public and semi-public spaces (street and pubs) of the urbanised municipalities of Brussels during their free time. Their involvement in violent interactions with their friends or wives – an assertion of their male identity or a release of physical energy – displeases authority figures, who convey middle-class standards of behaviour and intervene in an attempt to re-establish order. People with different ways of behaving clash in public as they try to impose their way of being. Police activity contributes to the criminalisation of working-class forms of social life and leisure.